2013
DOI: 10.1242/jeb.083089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraspecific variation in reproductive traits, pectoral fin use and burst swimming on metabolic rates and swimming performance: a study on the Trinidadian guppy (Poecilia reticulataPeters)

Abstract: SUMMARYThere is considerable intraspecific variation in metabolic rates and locomotor performance in aquatic ectothermic vertebrates; however, the mechanistic basis remains poorly understood. Using pregnant Trinidadian guppies (Poecilia reticulata), a livebearing teleost, we examined the effects of reproductive traits, pectoral fin use and burst-assisted swimming on swimming metabolic rate, standard metabolic rate (M O2std ) and prolonged swimming performance (U crit ). Reproductive traits included reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 98 publications
1
52
0
Order By: Relevance
“…In fry rearing trial, Godavari and Krishna groups exhibited no significant difference between them, whereas both the populations exhibited significantly different performance as compared to Narmada population. Various studies have reported on the intra-specific variation in different reproductive parameters in fishes viz., Poecilia reticulata (Peters, 1860) (Svendsen et al, 2013); Lacerta vivipara (Von Jacquin, 1787) (Bauwens and Verheyen, 1987) and in several European freshwater fishes (Blanck et al, 2007). The present findings in magur from Indian rivers indicate variations in reproductive parameters between populations of same species.…”
Section: Resultsmentioning
confidence: 49%
“…In fry rearing trial, Godavari and Krishna groups exhibited no significant difference between them, whereas both the populations exhibited significantly different performance as compared to Narmada population. Various studies have reported on the intra-specific variation in different reproductive parameters in fishes viz., Poecilia reticulata (Peters, 1860) (Svendsen et al, 2013); Lacerta vivipara (Von Jacquin, 1787) (Bauwens and Verheyen, 1987) and in several European freshwater fishes (Blanck et al, 2007). The present findings in magur from Indian rivers indicate variations in reproductive parameters between populations of same species.…”
Section: Resultsmentioning
confidence: 49%
“…The flush pump was controlled by AutoResp software (version 2.1.3; Loligo Systems, Tjele, Denmark) that also calculated the M O 2 in the measurement phase using the oxygen partial pressure and standard equations [42], [43]. Preliminary testing demonstrated that the duration of the measurement phase (3 min) ensured that the coefficient of determination (r 2 ) associated with each M O 2 measurement was always>0.95, similar to previous studies [44]. Corrections of background respiration (i.e.…”
Section: Methodsmentioning
confidence: 52%
“…Previous work in guppies has demonstrated that intraspecific variation in use of the pectoral fins during swimming is associated with increased energy expenditure at a given speed (Svendsen et al . ). Our results suggest that the presence of male harassment within a guppy population can alter the degree of variation in swimming mechanics present among females, thus decreasing their costs of locomotion.…”
Section: Discussionmentioning
confidence: 97%
“…The actual energetic cost of pectoral fin movements during subcarangiform swimming is relatively small (Gerry & Ellerby ), but the pectoral fins are used to stabilize the fish during forward movement, and excessive fin movement is probably a general indicator of suboptimal and apparently inefficient swimming mechanics (Svendsen et al . ). We found no evidence for plasticity in the capacity for aerobic metabolism at either the whole‐animal (MMR, AS) or biochemical level (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation